Analisis Faktor- Faktor Pengelolaan Barang Milik Negara Pada Komisi Pemilihan Umum Provinsi Sulawesi Utara - Tulungen, Evans Einstein William (JURNAL RISET BISNIS DAN MANAJEMEN, 2014)
This study aims to analyze the factors of asset management at the Provincial Election Commission of North Sulawesi. The study was conducted using quantitative descriptive method. The method used is associative where research aims to determine the relationship between two or more variables. The analysis technique used is factor analysis. Based on the test results of the data analysis it was found that the testing of the 33 factors in the management of assets in the Provincial Election Commission and District / City-North Sulawesi, then there are 19 factors that declared invalid meets Kaiser Meyer Olkin (KMO) and 14 factors revealed no meet the KMO test results with values ​​below 0.5. After testing a factor rotation using the varimax method of factor analysis in this study the data were grouped into factors that Safeguarding and Maintenance of State property, the State Property Planning, Administration of State Assets, Use of State Assets and Technical Guidance State Property. Keyword : Managent, assets management, Guidance State Property